Trends in Anemia and Iron Deficiency in India, Jammu & Kashmir, and Regional Peers (2020–2025): A Multi-Source, Programmatic Evaluation - Jayachandran Gopi; Shivam Sharma; Shounak Nandy; Krishnareddy; Kamaljot Singh; Nitesh Kumar; Prateek Bobhate (The Bioscan, 2025)
Anemia and iron deficiency anemia (IDA) remain pervasive in India and South Asia, impacting women, adolescents, and young children and undermining health and economic growth. The Anemia Mukt Bharat (AMB) initiative, under India’s POSHAN Abhiyaan, targets substantial reductions by 2025. Objectives: To analyze five-year national and state trends in anemia and IDA coverage indicators, with an in-depth focus on Jammu & Kashmir, and benchmark progress against peer regions. Methods: We synthesized national scorecard data, NFHS surveys, implementation studies, and regional meta-analyses from 2020–2025. Coverage, compliance, and program innovation were evaluated across populations and regions, including comparative analysis with Pakistan and Sub-Saharan Africa. Results: India achieved strong coverage gains for pregnant women (95% IFA supplementation) and improvements among adolescents and lactating mothers. Jammu & Kashmir demonstrated striking convergence with the national average post-2021, benefitting from localized intervention. Notable gaps persist in young children (6–59 months) and adolescent girls, exacerbated by compliance, behavioral, and structural challenges. Rajasthan’s “Shakti Divas” proved high impact for adolescent supplementation but flagged sustainability issues. In comparison, Pakistan and Sub-Saharan Africa retain high prevalence, underscoring regional barriers.